Skała Izraela w świetle wiersza Pwt 32, 18 - Szwarc, Urszula (The Biblical Annals, 2017)
The paper presents an analysis of Dtn 32,6.10-12.13b.18. Its aim is to define what the inspired author understood by the term ’Rock’ in Dtn 32,18. The research conducted by the author allows stating the fact of Divine parenthood of the Rock of Israel, identified with Jhwh, with relation to the chosen nation. It also makes it possible to define what it consists in. According to the discussed verses, this reality is expressed in the act of giving birth, in the meaning of creating an exceptional − in the history of mankind − nation from not very significant tribes. It is also shown in the Rock-Parent’s constant and unconditional protection provided to Israel. This may be seen in various ways: supporting the existence of the chosen nation, instructing and directing it, protecting it from threats, saving it from danger.